2019
DOI: 10.1080/17461391.2019.1656781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental fatigue on passing decision‐making performance in professional soccer athletes

Abstract: The aim of this study was to analyse the effect of mental fatigue on passing decision-making in professional soccer athletes. A controlled and counterbalanced cross-over design was adopted consisting of three visits with a 1-week interval between sessions. Twenty professional soccer male athletes participated in three randomized conditions divided into three visits: control, 15-min Stroop task, and 30-min Stroop task. Inhibitory control was accessed by the Stroop task (accuracy and response time) before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 48 publications
6
108
4
2
Order By: Relevance
“…Moreover, they considered accelerations >2.78 m/s 2 , while we considered those >2 m/s 2 . The fact that MF could negatively impact players' ability to accelerate for a certain distance may be of practical importance and reinforce the advice that highly demanding-cognitive task should be avoided before a soccer-specific activity (e.g., SSG or match-play) [13]. On one hand, it might be argued that if mentally fatigued players lose more balls and fail more dribbles, they would be expected to perform more accelerations to compensate the decrease of their technical performance.…”
Section: Soccer-specific Decision-making Performancementioning
confidence: 73%
See 4 more Smart Citations
“…Moreover, they considered accelerations >2.78 m/s 2 , while we considered those >2 m/s 2 . The fact that MF could negatively impact players' ability to accelerate for a certain distance may be of practical importance and reinforce the advice that highly demanding-cognitive task should be avoided before a soccer-specific activity (e.g., SSG or match-play) [13]. On one hand, it might be argued that if mentally fatigued players lose more balls and fail more dribbles, they would be expected to perform more accelerations to compensate the decrease of their technical performance.…”
Section: Soccer-specific Decision-making Performancementioning
confidence: 73%
“…The present study is the first to document the detrimental effect of mental fatigue on soccer-specific decision-making skills during SSG. To the extent of the authors’ knowledge, to date, only the study of Gantois et al [ 13 ] examined the effects of mental fatigue on decision-making skills (i.e., on passing decision-making skill) under an ecological environment. The authors found that passing decision-making performance in male professional soccer players declined during a 90-min training match and after a prolonged (15–30 min) cognitive task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations